Cross-cultural adaptation and validation of the PRISMA-7 scale for European Portuguese - Santiago, Luiz Miguel; Silva, Raquel; Velho, Denise; Rosendo, Inês; Simões, José (Family Medicine & Primary Care Review, 2020)
Background . Frailty is an age-associated biological syndrome and a predictor of multimorbidity outcomes, whose early recognition allows for the identification of those older patients at risk. The PRISMA-7 scale allows for the identification of frail older people. Objectives . To make a cross-cultural adaptation and validation of the PRISMA-7 to the European spoken Portuguese language. Material and methods . Cross-cultural adaptation by translation of the PRISMA-7 scale into European Portuguese, debriefing and back-translation to English. Application for intra-observer reliability assessment and validation by simultaneous and concurrent application of the Katz scale. Results . Cronbach’s alpha coefficient was of 0.420 and 0.409 after a re-test. Spearman’s Rank Order Correlation of 0.969 in the re-test operation in a sample of 64 older people (35 female). More than 3 affirmative answers were found for older people (p < 0.001), for a higher number of self-reported drugs taken, (p = 0.001), self-reported years of education (p = 0.001), higher values for those with less years of studies were found in the validation of the translated PRISMA-7 scale, in a purposive sample of 127 older people, 72 (56.7%) female. No differences were found between gender (p = 0.414) and for number of self-reported diseases (p = 0.258). A Spearman correlation of ρ = 0.477 (p < 0.001) between the total of the two scales was found. Discussion . This comprehensive tool enables health care providers to discuss and architect more effective and efficient measures for these patients’ care, regardless of gender, socio-demographic factors, number of self-reported drugs taken and diseases. Conclusions . The PRISMA-7 scale is now recommended to identify frail older people in the Portuguese community.